Comprehensive investigating of MMR gene in hepatocellular carcinoma with chronic hepatitis B virus infection in Han Chinese population - Ma, Ning; Jin, Ao; Sun, Yitong; Jin, Yiyao; Sun, Yucheng; Xiao, Qian; Sha, XuanYi; Yu, Fengxue; Yang, Lei; Liu, Wenxuan; Gao, Xia; Zhang, Xiaolin; et al. (Frontiers in Oncology, 2023)
Hepatocellular carcinoma associated with chronic hepatitis B virus infection seriously affects human health. Present studies suggest that genetic susceptibility plays an important role in the mechanism of cancer development. Therefore, this study focused on single nucleotide polymorphisms (SNPs) of MMR genes associated with HBV-HCC. Five groups of participants were included in this study, which were healthy control group (HC), spontaneous clearance (SC), chronic hepatitis B group (CHB), HBV-related liver cirrhosis group (LC) and HBV-related hepatocellular carcinoma group (HBV-HCC). A total of 3128 participants met the inclusion and exclusion criteria for this study. 20 polymorphic loci on MSH2, MSH3 and MSH6 were selected for genotyping. There were four case-control studies, which were HC vs. HCC, SC vs. HCC, CHB vs. HCC and LC vs. HCC. We used Hardy-Weinberg equilibrium test, unconditional logistic regression, haplotype analysis, and gene-gene interaction for genetic analysis. Ultimately, after excluding confounding factors such as age, sex, smoking and drinking, 12 polymorphisms were found to be associated with genetic susceptibility to HCC. We speculated on the possible biological mechanisms of 4 polymorphisms, including three risk factors (MSH3-rs26779, MSH3-rs181747 and MSH3-rs32950) and one protected factor (MSH2-rs4952887). Haplotype analysis showed the risk haplotype GTTT (rs1805355_G, rs3776968_T, rs1428030_C, rs181747_C) was more frequent in the HCC group compared with the HC group. The GMDR analysis showed that the best interaction model was the three-factor model of MSH2-rs1981928, MSH3-rs26779 and MSH6-rs2348244 in SC vs. HCC group(P=0.001). In addition, we found multiplicative or additive interactions between genes in our selected SNPs. These findings provide new ideas to further explore the etiology and pathogenesis of HCC.